Excellent Service Management For Pandean Tourism Village Destinations In Trenggalek - Sulistiyanto Sulistiyanto; Budi Rianto; Edi Suhardono; Laurentia Tri Lestari (Jurnal Manajemen Pelayanan Publik, 2023)
The development of Pandean tourist village service management has succeeded in enhancing the village's superiority in the tourist village award competition in 2022 so many best practices can be analyzed regarding the success of the local community and village government in managing the tourist village. In this research, the 6A approach was used, Attraction, Amenities, Ancillary, Activity, Accessibilities, and Available Packages (Chaerunissa & Yuniningsih, 2020) to study the development of excellent tourism services in the Pandean tourist village. The purpose of this research is to describe and analyze how excellent service management is conducted by the village government together with the local community, especially the Dewi Arum Pulosari Tourism Awareness Group community organization in Pandean Village in providing services in the Pandean tourist village. The method applied is qualitative descriptive research regarding various activities carried out by the local village government, especially the tourism awareness group which is assigned the main tasks and functions of tourism services in the village by the local village government. The results show that the application of the 6A theory can be implemented well so that it can make Pandean Tourism Village one of the best tourist villages at the national level in 2022 regarding the 7 assessment indicators provided by the Indonesian Tourism Village Association.